Teaching and assessing consultation skills: an evaluation of a South African workshop on using the Leicester Assessment Package - A. Hastings; D. Cameron; E. Preston-Whyte (South African Family Practice)
Background: The consultation is at the very centre of clinical practice. It is in the meeting between doctor and patient that the story is told (and in good practice properly heeded) and decisions are made about the cause and treatment of the patient's problem. Following one year of supervised internship, South African doctors are required to do a year of community service and these doctors mostly work in understaffed peripheral hospitals. A substantial component of this work is unsupervised consultations with patients suffering from new or complex continuing diseases. On graduation, these doctors therefore require a high level of consultation competence. They must be able to make accurate diagnoses and manage patients' problems reliably and efficiently. The Leicester Assessment Package (LAP) was originally developed to assess the consultation competence of general practitioners in the UK. It was subsequently adapted for use in undergraduate teaching. In 2002, the LAP was presented at a medical education conference in South Africa. As a result, the Department of Family Medicine at Pretoria University began using the LAP in the teaching and formative assessment of the consultation skills of senior students in outpatient clinics. In 2003, the University of the Witwatersrand introduced a four-year graduate entry medical curriculum. The Centre for Health Care Education was interested in assessing whether the LAP would be suitable for the summative assessment of the consultation performance of students during their third and four years of the new curriculum.A workshop course was organised to train senior clinicians from the Universities of Pretoria and the Witwatersrand in the use of the LAP as a means of teaching and assessing the consultation performance of South African medical students.